Global labour, global business, global crisis. (6th June 2012) - Boffo, Marco; Haynes, Michael
This paper contextualises this special issue of the IJMCP on global labour by surveying the state of formation of the global labour force. Drawing on ILO data it distinguishes several groups within the global labour force. It notes problems in measuring the size of these groups and the debates about their nature and draws attention to the contributions of the papers that follow. It then considers how the global crisis that began in 2008 is affecting the global labour force and the light thrown on this by the papers in this issue.